METHODS OF TEACHING ENGLISH TO PRIMARY STUDENTS WITH HEARING DISABILITIES USING ROLE PLAYS (The Role of Exact Sciences in the Era of Modern Development, 2025)
This article highlights the positive impact of utilizing role-playing activities in elementary classes, emphasizing the importance of fostering creativity and developing social-emotional skills among students.